Implementasi Inovatif Kampus Mengajar Untuk Menumbuhkan Minat dan Tingkat Kreatifitas Sekolah Dasar - Sarah Maulina Octavia Malau (CV. ITTC INDONESIA, 2023)
This paper aims to find out the activities of the Teaching Campus implementation carried out by Practitioners in UPT. Teaching Campus is one of the activities taken by final students in fulfilling their duties and practices during lectures. The Teaching Campus of the University of North Sumatra Partners focuses on learning and teaching activities in basic education units from the Merdeka Belajar Kampus Merdeka (MBKM) program which aims to provide opportunities for students to learn and develop themselves through activities outside the classroom. The Teaching Campus aims to equip students with a variety of expertise and skills by partnering with teachers and schools in developing learning models, as well as fostering creativity and innovation in learning so that it has an impact on strengthening literacy and numeracy learning in schools. In this paper, we will describe how the stages of getting grade 5 students of SDN 060810 Jl Halat to be creative and like the learning that is presented.